The chemical chaperone sodium 4-phenylbutyrate improves the secretion of the protein CA267T mutant in CHO-K1 cells trough the GRASP55 pathway. Issue 1 (December 2015) - Chollet, Maria; Skarpen, Ellen; Iversen, Nina; Sandset, Per; Skretting, Grethe
Abstract Some inherited coagulation factor deficiencies are caused by intracellular retention or degradation of misfolded proteins, and chemical chaperones have been shown to reverse protein misfolding. The purpose of the present study was to investigate whether chemical chaperones may improve secretion of the protein CA267T (PCA267T ) mutant in a cellular model. Using stably transfected Chinese hamster ovary cells (CHO-K1) expressing PCA267T we demonstrate that sodium 4-phenylbutyrate (PBA) increased the secretion of PCA267T by approximately 4-fold in comparison with untreated cells, and that this secretion seemed to follow an unconventional pathway via the Golgi reassembly stacking protein (GRASP55).